2012
DOI: 10.3409/fb60_3-4.235-241
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Dietary Selenium Source on Embryonic Development in Turkeys

Abstract: The objective of this study was to determine the effect of dietary selenium source on the growth and development of turkey embryos, and egg hatchability. White broad-breasted BUT Big 6 turkeys (1800 females and 150 males) were placed under optimum management conditions. Turkey diets were supplemented with organic selenium, and in the other with inorganic selenium, in the amount of 0.3 ppm. Eggs intended for incubation and examination were collected in week 2, 10, 18 and 23 of the laying season. The average egg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Payne et al (2005), whose results are consistent with our findings, observed a linear increase in egg weight as dietary Se levels increased. In a study by Stępińska et al (2012), the average egg weight was higher in turkey hens fed a diet with organic selenium than in layers receiving inorganic selenium.…”
Section: Discussionmentioning
confidence: 94%
“…Payne et al (2005), whose results are consistent with our findings, observed a linear increase in egg weight as dietary Se levels increased. In a study by Stępińska et al (2012), the average egg weight was higher in turkey hens fed a diet with organic selenium than in layers receiving inorganic selenium.…”
Section: Discussionmentioning
confidence: 94%
“…Embryonic growth in precocial birds has been widely investigated, for instance duck (Tangara et al, 2010), turkey (Stepińska et al, 2012), and chicken (Li et al, 2014). In contrast to precocial poultry, young pigeons, a typical representative of altricial birds, are feed with pigeon milk from the crop by parents for a few days.…”
Section: Introductionmentioning
confidence: 99%
“…Stepinska et al . (2012) investigated the influence of dietary Se sources on the growth and development of turkey embryos. They found that the average egg weight was higher in laying hens fed organic Se than those receiving inorganic Se.…”
Section: Development Of Se‐rich Foodmentioning
confidence: 99%
“…in animal feed and accumulate organic Se compounds in the body through animal enrichment to obtain Se-enriched products, such as Seenriched dairy products, Se-enriched eggs, Se-enriched honey, and Se-enriched meat products. Stepinska et al (2012) investigated the influence of dietary Se sources on the growth and development of turkey embryos. They found that the average egg weight was higher in laying hens fed organic Se than those receiving inorganic Se.…”
Section: Animal Transformation Of Sementioning
confidence: 99%